Mechanical and Thermal Properties of Interlocking Bricks utilizing wasted Polyethylene Terephthalate (PET) - Vivekka , Olivia John (IRC, 2019)
Plastic bottles are non-biodegradable which made from Polyethylene Terephthalate (PET) and takes about 450 years to decompose. In Malaysia only, about 13.2% of plastics contribute to municipal solid waste and 2.5% of it are Polyethylene Terephthalate (PET). Therefore, there is increasing demand in finding a possibility in recycling and applying the plastic bottles into civil engineering application. To solve the increasing amount of plastic bottles waste causing environmental problems, interlocking bricks made of waste plastic bottles are used to replace the conventional bricks that use cement and clay.